The Influence of Service Quality and Price on Customer Loyalty in CV. Yes service - Halim Dinata; Muhammad Fauzan Azhmy; Saskia (Outline Journal of Economic Studies, 2022)
The purpose of this study was to analyze the effect of service quality and price on customer loyalty at CV. Yes Service. The data used are primary data and secondary data. Primary data was collected through questionnaires distributed to employees, while secondary data was obtained from documentation studies obtained from various information held by the company and the results of previous research. The data analysis method uses quantitative methods, namely Multiple Linear Regression analysis. The population in this study were customers of CV. Yes Service. The sample in this study were 110 respondents. The results showed that Service Quality (X1) and Price (X2) on Customer Loyalty, it was concluded that there was a positive and significant influence between Service Quality and Price together on Customer Loyalty. While the ability of Service Quality (X1) and Price (X2) together can explain changes in Customer Loyalty (Y) of 43.3% while the remaining 56.7% is influenced by other factors not discussed in this study